Effects of Peptide C12-OOWW-NH2 on Transcriptome and Cell Wall of the Postharvest Fungal Pathogen Penicillium digitatum - Li, Xindan; Feng, Guirong; Wang, Wenjun; Yi, Lanhua; Deng, Lili; Zeng, Kaifang (Frontiers in Microbiology, 2020)
In this study, the transcriptional profiling of Penicillium digitatum after C12O3TR treatment was analyzed by RNA-Seq technology. A total of 2562 and 667 genes in P. digitatum were differentially expressed after 2 h and 12 h treatment, respectively. These genes were respectively mapped to 91 and 79 KEGG pathways. The expression patterns of differentially expressed genes (DEGs) at 2 h and 12 h were similar, mainly were the metabolic processes in cell wall, cell membrane, genetic information and energy. Particularly, cell integrity was the main metabolic process affected by C12O3TR stress for 2 h and 12 h, including cell wall and cell membrane. The changes of chitin in cell wall was observed by Calcofluor White (CFW) staining assay. The weaker blue fluorescence in the cell wall septa, the decrease in β-1, 3-glucan synthase activity and increase in chitinase and AKP activity showed that C12O3TR could damage the cell wall integrity. In conclusion, these results suggested that C12O3TR could inhibit the growth of P. digitatum through various mechanisms at transcriptional level, and could influence the cell wall permeability and integrity.